Making ICRF power compatible with a high-Z wall in ASDEX Upgrade. (27th October 2016) - Bobkov, V; Aguiam, D; Bilato, R; Brezinsek, S; Colas, L; Faugel, H; Fünfgelder, H; Herrmann, A; Jacquot, J; Kallenbach, A; Milanesio, D; Maggiora, R; et al.
Abstract: A comparison of the ASDEX Upgrade 3-strap ICRF antenna data with the linear electro-magnetic TOPICA calculations is presented. The comparison substantiates a reduction of the local electric field at the radially protruding plasma-facing elements of the antenna as a relevant approach for minimizing tungsten (W) sputtering in conditions when the slow wave is strongly evanescent. The measured reaction of the time-averaged RF current at the antenna limiters to the antenna feeding variations is less sensitive than predicted by the calculations. This is likely to have been caused by temporal and spatial fluctuations in the 3D plasma density distribution affected by local non-linear interactions. The 3-strap antenna with the W-coated limiters produces drastically less W sputtering compared to the W-coated 2-strap antennas. This is consistent with the non-linear asymptotic SSWICH-SW calculations for RF sheaths.